The mediating role of competitive advantage in the relationship between entrepreneurial leadership and financial performance in Indonesian private higher education / Siti Samsiah ... [et al.] - -, Siti Samsiah; Nik Muhammad, Nik Maheran; Hetri Suriyanti, Linda; Zainuddin, Siti Afiqah; -, Siti Rodiah (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2024)
In a highly competitive and dynamic setting, the notion of entrepreneurial leadership is essential. The development of a competitive advantage that will eventually enhance an organization's financial performance requires entrepreneurial leadership qualities. In this study, the relationship between financial performance (FP) and entrepreneurial leadership (EL) in private universities in Indonesia was investigated experimentally via the lens of competitive advantage (CA) mediation. The results of this investigation showed that EL positively impacts both CA and FP. The questionnaire survey included 124 respondents, and SmartPLS 4.1.0.3 was used for analysis. Furthermore, it was discovered that CA mediated the link between FP and EL. The conclusions highlight how private universities may greatly increase their competitive edge by fostering entrepreneurial leadership, which will also enhance their financial performance. University leaders are advised to adopt leadership strategies that revolve around vision and mission, creativity and innovation, passion and perseverance, opportunity focus, risk-taking, capacity building, and trust in facing market challenges to create a sustainable competitive advantage and improve their institution's financial results.